2006
DOI: 10.1086/498407
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Early Optical Emission at Gamma‐Ray Burst Locations by theSolar Mass Ejection Imager(SMEI)

Abstract: The Solar Mass Ejection Imager (SMEI) views nearly every point on the sky once every 102 minutes and can detect point sources as faint as R~10 th magnitude. Therefore, SMEI can detect or provide upper limits for the optical afterglow from gamma-ray bursts in the tens of minutes after the burst when different shocked regions may emit optically. Here we provide upper limits for 58 bursts between

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…8 in Eyles et al (2003)), but has about a 0.5°diameter extent. The short-term differential photometric precision is 0.1% over most of the sky, but degrades near bright stars or the Moon, during periods of bright aurora (Mizuno et al, 2005) or when auroral electrons or South Atlantic Anomaly (SAA) protons impact the CCD (Buffington et al, 2006a). The SMEI data are originally recorded in the form of per-pixel electron counts from the CCD detector that are labeled analog-todigital units (ADUs) in the various SMEI publications.…”
Section: Smei Observations and Data Analysesmentioning
confidence: 99%
“…8 in Eyles et al (2003)), but has about a 0.5°diameter extent. The short-term differential photometric precision is 0.1% over most of the sky, but degrades near bright stars or the Moon, during periods of bright aurora (Mizuno et al, 2005) or when auroral electrons or South Atlantic Anomaly (SAA) protons impact the CCD (Buffington et al, 2006a). The SMEI data are originally recorded in the form of per-pixel electron counts from the CCD detector that are labeled analog-todigital units (ADUs) in the various SMEI publications.…”
Section: Smei Observations and Data Analysesmentioning
confidence: 99%
“…The image pixels are 0.5° bins with a resolution of ∼1°. At this level of processing each image bin is the average of approximately 10 CCD frames providing an RMS sensitivity of ∼0.1 ADU [ Buffington et al , 2006].…”
Section: Smei Instrument and Data Processingmentioning
confidence: 99%
“…SMEI was capable of detecting stars (at a 3σ threshold within a square-degree bin) down to 10th magnitude in a single sky map (Buffington et al 2006a). The resulting numerous stars therefore dominated the FOV of each camera.…”
Section: Astronomical Factorsmentioning
confidence: 99%
“…Also Spreckley and Stevens (2008) studied Polaris and provided valuable light curves for further stellar work, and Tarrant et al (2008aTarrant et al ( , 2008bTarrant et al ( , 2008c reported on oscillations in β Ursae Minoris and γ Doradus, and asteroseismology of red giant stars, respectively. Finally, SMEI searched for corresponding optical signatures for gamma-ray bursts (Buffington et al 2006a). However, there were no detections at the sensitivity limit of SMEI.…”
Section: Variable Starsmentioning
confidence: 99%